28 days - Topping, Jenno; Thomas, Betty ([Culver City, CA] : Columbia Pictures Industries, 2000)
A high-flying party girl gets herself a DUI and 28 days in rehab -- and ends up discovering that real happiness must come from within
Writer, Susannah Grant
Cast: Sandra Bullock, Viggo Mortensen
VCD format
Keywords: Drugs in motion pictures; Alcoholism in motion picture